2018
DOI: 10.1002/lno.10963
|View full text |Cite
|
Sign up to set email alerts
|

Photophysiology of nitrate limited phytoplankton communities in Kongsfjorden, Spitsbergen

Abstract: In Arctic coastal regions, the phytoplankton bloom is often initiated by meltwater induced stratification in spring, while subsequent nutrient depletion is believed to drive phytoplankton succession in summer. The associated changes in photophysiology are difficult to identify, because these can be governed by acclimation to light and nutrient availability as well as variations in phytoplankton biomass and taxonomic composition. In the present study, the consequences of nutrient limitation for photophysiology … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 56 publications
(113 reference statements)
8
16
0
Order By: Relevance
“…It needs to be noted that C : N ratios were enhanced in all MSR treatments relative to the start community, but did not display any CO 2 ‐dependent changes (Table ). Considering also that nitrate limitation did not affect carbon buildup in previous studies (Lancelot and Mathot ; Davidson et al ; Deppeler et al ; Kulk et al ; van de Poll et al ), we suggest that transient nitrate drawdown did not negatively influence PP. Such changes in productivity did further not translate into changes in species composition, as the latter was similar between the start and the end of the first experimental phase (Fig.…”
Section: Discussionsupporting
confidence: 52%
“…It needs to be noted that C : N ratios were enhanced in all MSR treatments relative to the start community, but did not display any CO 2 ‐dependent changes (Table ). Considering also that nitrate limitation did not affect carbon buildup in previous studies (Lancelot and Mathot ; Davidson et al ; Deppeler et al ; Kulk et al ; van de Poll et al ), we suggest that transient nitrate drawdown did not negatively influence PP. Such changes in productivity did further not translate into changes in species composition, as the latter was similar between the start and the end of the first experimental phase (Fig.…”
Section: Discussionsupporting
confidence: 52%
“…Zhu et al (2019) also reported that the F v / F m in the Chukchi Borderland was approximately 24% lower than in the CS waters, which was similar to the results of this study. Meanwhile, the F v / F m observed off the coast of the Arctic Ocean is known to remain high (≥0.50) throughout the year, except immediately after the spring bloom (Aardema et al, 2019; Kulk et al, 2018; McMinn & Hegseth, 2004; Mills et al, 2018; Mosharov et al, 2019). This study also showed high phytoplankton F v / F m values (0.56) in Arctic coastal waters in the summer, indicating the lack of nutrient stress.…”
Section: Discussionmentioning
confidence: 99%
“…These long‐term incubations revealed that F v / F m and ETR max increased by 12 ± 9% and 40 ± 17%, respectively, and the fraction of large (≥10 μm) phytoplankton increased by approximately 25% compared to the beginning of culture sample (Figure 11). In turn, larger cells fraction exhibited increased photosynthetic capacity (Kulk et al, 2018; Mills et al, 2018). Mills et al (2018) reported an increase in the large‐sized diatom biomass in response to nitrate enrichment in the Chukchi Sea.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We similarly recently reported that variance of K C , derived from parallel measures of FRRf-derived ETRs and C-uptake rates, could be generally explained by patterns in light availability (Zhu et al, 2016), but importantly was much improved when considering differences in phytoplankton size structures (Zhu et al, 2017). In fact, changes in predominant species within phytoplankton communities appears to be a factor increasingly important in explaining patterns of K C (e.g., Kulk et al, 2018;Xie et al, 2018), likely reflecting selection of taxa by environmental factors that are not specifically measured as part of the assessment exercise of interest (see Hughes et al, 2018a). Patterns of K C variability over space and time therefore remain problematic to fully resolve.…”
Section: Introductionmentioning
confidence: 90%